Factors Related to The Incidence of Postpartum Blues In Post-Partum Mothers in The Working Area of Plumbon Community Health Center - Rezani, Nadia; Widayanti, Wiwin; Suminar, Erni Ratna; Rahmatika, Siti Difta (Jurnal Medisci, 2025)
Background: The current state of postpartum blues is very concerning, as it can lead to long-term psychological consequences, including postpartum depression. According to 2024 data from the National Population and Family Planning Board (BKKBN), 57% of mothers in Indonesia experience postpartum blues symptoms. Aims. The purpose of this research is to determine the factors related to the occurrence of postpartum blues in the Plumbon Community Health Center work area. Method used quantitative observational analysis with a cross-sectional approach. The population in this study was postpartum women on days 1-7. The sampling technique used was consecutive sampling. Data were collected using the EPDS questionnaire and the husband's support questionnaire. Results showed a significant relationship between the husband's support and the occurrence of postpartum blues (p value 0.000), and no relationship between age (p value 0.368), education (p value 0.114), and the occurrence of postpartum blues. Conclusion. This study concludes that the husband's support is significantly associated with postpartum blues (p-value = 0.000). Implementation it is hoped that further research can examine more factors such as knowledge of postpartum mothers, economic status, and occupation.